Modern Photography - Norton, M.A. (My University, 1897)
Introduction: The possibilities of photography are great. Only one hundred and seventy years have passed since the first photograph was taken. It was the wonderful reproduction of a bit of string about a glass. Today we reproduce on paper all the motions of an insect flying in the sunlight; photograph the bones of the human body through the living flesh, bring the most distant stars before us in permanent record; we have photographed the compressed air before a flying bullet; and some even profess to have secured photographs of those most evanescent of things, the spirits of their departed friends and the thoughts emanating from their own brains—what may we not hope to accomplish in years to come.
Citation: Norton, M.A. Modern Photography. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: History; Photography; Theses; Manuscripts (documents)